Toward Better Understanding of Turbulence Effects on Bridge Aerodynamics - Cao, Shuyang; Cao, Jinxin (Frontiers in Built Environment, 2017)
With the trend of variable cross-sections for long-span bridges from truss-stiffened to quasi-streamlined, and then to multiple-box cross-section geometries, the importance of aeroelastic performance is becoming increasingly significant in wind-resistant design. This article shows that there is clearly insufficient qualitative as well as quantitative understanding of turbulence effects on bridge aerodynamics, particularly the mechanisms behind them. Although turbulence might help the stabilization of long-span bridges, and is thus not a conclusive parameter in wind-resistant design, turbulence effects on the aerodynamic and aeroelastic behaviors of a bridge need to be better understood because interaction between a bridge and turbulence always exists. This article also briefly introduces a newly developed multiple-fan wind tunnel that is designed to control turbulence to assist the study of turbulence effects.